Keetmanshoop office (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
31 JPEG and 3 pdf files documenting participant observation at the Swakara office in Keetmanshoop
Keywords: Karakul sheep; Breeding; Management; Agriculture; Postcolonialism; South Africa; Colonisation; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Germany; Colonial South-West Africa; German Colonialism; Karakul Sheep Industry